The colonisation of Setswana: A decolonial rereading of the 1840 Gospel of Luke - Mothoagae, Itumeleng D. (HTS teologiese studies, 2024)
In his 1840 translation of the Gospel of Luke from English into Setswana, Robert Moffat transfers Western numerals, geographic words and biblical names to Setswana. In this article, it is argued that in this translation, we see the beginning of the colonisation of Setswana. Furthermore, it is argued that in this translation, Moffat used epistemic privilege and the performance of power to facilitate the process of epistemicide on the linguistic heritage of Batswana and its indigenous knowledge system through an act of colonisation.Contribution: The article applies an intersection of theoretical lenses, namely decoloniality and the Foucauldian notion of power, as its frames of reference in analysing the 1840 English–Setswana Gospel of Luke.